In vitro assessment of Neuronal PAS domain 2 mitigating compounds for scarless wound healing - Clements, Adam; Shibuya, Yoichiro; Hokugo, Akishige; Brooks, Zachary; Roca, Yvonne; Kondo, Takeru; Nishimura, Ichiro; Jarrahy, Reza (Frontiers in Medicine, 2023)
Background The core circadian gene Neuronal PAS domain 2 (NPAS2) is expressed in dermal fibroblasts and has been shown to play a critical role in regulating collagen synthesis during wound healing. We have performed high throughput drug screening to identify genes responsible for downregulation of Npas2 while maintaining cell viability. From this, five FDA-approved hit compounds were shown to suppress Npas2 expression in fibroblasts. In this study, we hypothesize that the therapeutic suppression of Npas2 by hit compounds will have two effects: (1) attenuated excessive collagen deposition and (2) accelerated dermal wound healing without hypertrophic scarring. Materials and methods To test the effects of each hit compound (named Dwn1, 2, 3, 4, and 5), primary adult human dermal fibroblasts (HDFa) were treated with either 0, 0.1, 1, or 10 μM of a single hit compound. HDFa behaviors were assessed by picrosirius red staining and quantitative RT-PCR for in vitro collagen synthesis, cell viability assay, in vitro fibroblast-to-myofibroblast differentiation test, and cell migration assays. Results Dwn1 and Dwn2 were found to significantly affect collagen synthesis and cell migration without any cytotoxicity. Dwn3, Dwn4, and Dwn5 did not affect collagen synthesis and were thereby eliminated from further consideration for their role in mitigation of gene expression or myofibroblast differentiation. Dwn1 also attenuated myofibroblast differentiation on HDFa. Conclusion Dwn1 and Dwn2 may serve as possible therapeutic agents for future studies related to skin wound healing.